Analisis Pengaruh Content Marketing, Brand Image, E-Wom, dan Customer Engagement terhadap Purchase Intention Parfum Lokal di Jakarta - Ahmad Fahmi; Usep Suhud; Rizka Zakiah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
In recent years, perfume sales in Indonesia have been experiencing rapid growth. This potential development has emerged as a result of increasing public awareness of the importance of maintaining personal appearance. Data shows that Indonesians now prefer to buy local or domestic products to maintain their appearance, leading to intense market competition among local perfume brands. This study aims to analyze the influence of content marketing on brand image, electronic word of mouth (e-WOM), and customer engagement, as well as the influence of brand image, electronic word of mouth, and customer engagement on purchase intention in the context of local perfumes in Jakarta. This research uses a quantitative method by collecting data through a Google Form questionnaire distributed to 210 respondents. The criteria for respondents in this study include Jakarta residents aged 17 and above who have used local perfumes and have seen content related to local perfume brands. The study employs structural equation modeling analysis techniques using SPSS 25 and Amos 23 software. The results of this study indicate that content marketing has a positive and significant effect on brand image, electronic word of mouth, and customer engagement. Furthermore, it is also found that brand image, electronic word of mouth, and customer engagement have a positive and significant effect on purchase intention.